Implementasi Pembelajaran Intrakurikuler Projek Penguatan Profil Pelajar Pancasila di UPT SD Negeri 066050 Medan Denai - Anggun R. Gurning; Desi R.S Situmorang; Hotma U. Sitanggang; Ignasius Aritonang; Roi R. Manik; Tiara Agustin (STIKes Ibnu Sina Ajibarang, 2024)
This study is based on the reality that students still do not understand the diversity of culture, ethnicity and religion in Indonesia. Because the school environment generally consists of several relatively similar tribes and cultures, as well as the environment around the students' homes, which lacks cultural and ethnic diversity. With a relatively similar cultural and ethnic background around students, students are less familiar with the diversity in Indonesia, so it is feared that they will not have tolerance for differences, as the proverb says